1997
DOI: 10.1126/science.278.5345.1950
|View full text |Cite
|
Sign up to set email alerts
|

Spike Synchronization and Rate Modulation Differentially Involved in Motor Cortical Function

Abstract: It is now commonly accepted that planning and execution of movements are based on distributed processing by neuronal populations in motor cortical areas. It is less clear, though, how these populations organize dynamically to cope with the momentary computational demands. Simultaneously recorded activities of neurons in the primary motor cortex of monkeys during performance of a delayed-pointing task exhibited context-dependent, rapid changes in the patterns of coincident action potentials. Accurate spike sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
660
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 861 publications
(694 citation statements)
references
References 32 publications
32
660
2
Order By: Relevance
“…In the present study, the PM/MI neurons were trained similarly to the monkeys in the previous experiments (Riehle et al 1997(Riehle et al , 2000, as described below. In each learning trial, a cue signal appears at 100 msec to initiate the timed spikes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the PM/MI neurons were trained similarly to the monkeys in the previous experiments (Riehle et al 1997(Riehle et al , 2000, as described below. In each learning trial, a cue signal appears at 100 msec to initiate the timed spikes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies show that rate changes and synchronous firing of cortical neurons differentially engage in these cognitive functions. Riehle et al (1997) trained monkeys on a delayed response task in which a GO signal to instruct a motor response repeatedly followed a sensory cue at several possible, fixed delays. Spikes from pairs of premotor and primary motor (PM/MI) neurons coincided more frequently than expected by chance, particularly at those times when the monkeys were expecting the GO signal.…”
mentioning
confidence: 99%
“…Numerical simulations of FFNs showed that excitation of the first group of neurons with a volley of near synchronous spikes may result in increased synchrony of the spike volley, which remains stable in subsequent layers (Diesmann et al, 1999). Thus, propagating synchrony in the FFN has been proposed as a model to explain the occurrence of task-related precise spike patterns observed in behaving primates (Abeles et al, 1993;Nicolelis et al, 1995;Riehle et al, 1997;Prut et al, 1998). Asynchronous firing rates can be propagated through the FFN only in a restricted parameter regime (van Rossum et al, 2002), as the significant amount of shared connectivity among the neurons tends to synchronize the activity from one group to the next (Litvak et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A particularly important application in this respect concerns their use as control measurements against which to test multiple single-unit spike data for the presence of dynamic spike synchronization phenomena (Gerstein and Aertsen, 1985;Aertsen et al, 1987Aertsen et al, , 1989Riehle et al, 1997;Grü n et al, 1999).…”
Section: Discussionmentioning
confidence: 99%